Harriet Hardy and the Workers of Los Alamos: A Campus-Community Historical Investigation. (November 2014) - Silver, Ken; Bird, Rick; Smith, Alex; Valerio, Daniel; Romero, Hilario
Harriet Hardy, protégé of Alice Hamilton, spent 1948 in the Health Division of Los Alamos Scientific Laboratory. The contemporary campaign for federal legislation to compensate nuclear workers brought to the fore living retirees in whose cases of occupational illness Hardy had a role in diagnosis or case management. A third case is documented in archival records. Methods of participatory action research were used to better document the cases and strategize in light of the evidence, thereby assisting the workers with compensation claims. Medical and neuropsychological exams of the mercury case were conducted. Hardy's diary entries and memoirs were interpreted in light of medicolegal documentation and workers' recollections. Through these participatory research activities, Harriet Hardy's role and influence both inside and outside the atomic weapons complex have been elucidated. An important lesson learned is the ongoing need for a system of protective medical evaluations for nuclear workers with complex chemical exposures.